(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background Most spinal surgery is painful and good postoperative analgesia is important. Opioids are the traditional first-line treatment. Ketorolac has been used for postoperative pain relief. However, there is no data available about controlling postoperative pain with ketorolac after open lumbar discectomy or laminectomy in Bangladesah. Objective To compare the efficacy of a Parentral ketorolac with conventional opioid for management of postoperative pain after lumbar disectomy or laminectomy. Methods Sixty patients who underwent lumbar disectomy or laminectomy were randomly allocated into two groups. Group A (n = 30) patients received 30 mg intramuscular ketorolac upon surgical closure and every 6 hours for 24 hours and intramuscular pethidine 1.5 mg/kg/b.w. as needed (PRN). Group B (n = 30) patients received only intramuscular pethidine 1.5 mgkg-1/b.w. every 6 hours for 24 hours and as needed (PRN). Postoperative analgesia was assessed in both groups by Visual Analogue Scale at arrival in postoperative ward and at 6, 12 and 24 hours for 24 hours. Total postoperative narcotic consumption and side effects like post operative nausea and vomiting (PONV), dizziness, urinary retention and pruritus were also recorded. Results Baseline data were comparable between the two groups. The mean VAS almost similar and less than 3 at different reading in both groups which indicate adequate postoperative analgesia and the differences were statistically not significant. The mean total cumulative amount of pethidine administered over 24 hrs period was less in group A it was 64.31+19.13 mg where as in group B was 161.23+21.25 mg. and the difference was statistically significant (p<0.01). Incidences of side effects like PONV, urinary retention and pruritus were more in group B than group A and differences were statistically significant (p<0.01). Conclusion For postoperative pain management after lumbar spine surgery both ketorolac and traditional parental opioid found effective. Total opioid consumption is significantly less with ketorolac and side effects like PONV, dizziness, urinary retention and pruritus were more with opioid alone. DOI: http://dx.doi.org/10.3329/jbsa.v23i2.18175 Journal of BSA, 2009; 23(2): 56-61